Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Step One: Plug in (x-1) for y in 2x-y = 0
[tex]2x-(x-1)=0[/tex]
Step Two: Distribute the negative
[tex]2x -x -(-1)=0 \\ 2x-x+1=0[/tex]
Step Three: Add like terms on one side of the equation
[tex]x + 1=0[/tex]
Step Four: Subtract 1 from both sides
[tex]x+1-1=0-1 \\ x = -1[/tex]
Step Five: Plug x into one original equation (I chose y=x-1 but you can do either one)
[tex]y=x-1 \\ y=-1-1 \\ y=-2[/tex]
That's the answer to the problem, x = -1, y = -2 (-1,-2)!
Hope this helps!
[tex]2x-(x-1)=0[/tex]
Step Two: Distribute the negative
[tex]2x -x -(-1)=0 \\ 2x-x+1=0[/tex]
Step Three: Add like terms on one side of the equation
[tex]x + 1=0[/tex]
Step Four: Subtract 1 from both sides
[tex]x+1-1=0-1 \\ x = -1[/tex]
Step Five: Plug x into one original equation (I chose y=x-1 but you can do either one)
[tex]y=x-1 \\ y=-1-1 \\ y=-2[/tex]
That's the answer to the problem, x = -1, y = -2 (-1,-2)!
Hope this helps!
Step One: Plug in (x-1) for y in 2x-y = 0
Step Two: Distribute the negative
Step Three: Add like terms on one side of the equation
Step Four: Subtract 1 from both sides
Step Five: Plug x into one original equation (I chose y=x-1 but you can do either one)
That's the answer to the problem, x = -1, y = -2 (-1,-2)!
Hope this helps!
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.